Une approche de la sociolinguistique en Aragon - Alejandro Pardos Calvo; Antonio Eito Mateo; Chaime Marcuello Servós (Lengas)
The Aragonese language has been the subject of recurrent research from various perspectives over the past decades. This article proposes an overview of the most relevant sociolinguistic studies about this language. To start with, we focus on the studies concerning the Spanish spoken in Aragon and the initial perspectives generated around the Aragonese language, subordinate to the official language, Spanish. Next, we analyze the sociolinguistic production on the Aragonese language, spanning from early studies to the most recent ones. It is observed that the sole language specific to Aragon is undergoing an increasingly minority situation, with a weakened community of speakers and limited institutional support. Its scientific literature is much less extensive. However, it can be asserted that sociolinguistic research in Aragon includes relevant publications presenting data, reflections, and proposals that contribute to a better understanding of contemporary Aragonese and the tragic situation it faces.